Characteristics of Children With Kawasaki Disease-Like Signs in COVID-19 Pandemic: A Systematic Review - Mardi, Parham; Esmaeili, Marzieh; Iravani, Parisa; Abdar, Mohammad Esmail; Pourrostami, Kumars; Qorbani, Mostafa (Frontiers in Pediatrics, 2021)
Recent studies have shown several children diagnosed with COVID-19 have developed Kawasaki Disease (KD)-like symptoms. This systematic review aims to assess the demographic, laboratory, and clinical characteristics of children with KD-like syndrome during the COVID-19 pandemic and evaluate efficacy of treatments and patients’ outcome. A comprehensive search was carried out systematically through PubMed, Scopus, and Web of Science (WoS), medRxiv, and bioRxiv by two reviewers independently for all studies or preprints data on the demographic, laboratory and clinical characteristics of children with K.D-like signs during the COVID-19 outbreak. Overall, 39 studies were identified by the systematic search, of which 16 studies met inclusion criteria. The included studies involved 130 patients in total. Most of the included studies ( 93.7%) were case reports or case series, and in 12 (75%) of studies, patients were diagnosed with MIS-C. COVID-19 was diagnosed in 110 patients based on their polymerase chain reaction result, serological findings, and computed tomography results. Ninety-five patients had positive serological indices for COVID-19. Higher C-reactive protein and erythrocyte sedimentation rate level were the most prevalent laboratory findings (100%). In most studies, patients had leucopenia with marked lymphopenia, hypoalbuminemia, and increased ferritin, as well as hyponatremia. Abnormal echocardiography and respiratory outcome were the most clinical outcomes. In nine studies, all patients required intensive care unit admission, and only one death was reported across all studies. Findings of the present systematic review show that the incidence of KD-like syndrome in the COVID-19 pandemic increased significantly, which offers new insights in the KD pathogenesis and clinical spectrum.